Gilmar Ferreira Mendes, doctrinario y magistrado para la sociedad abierta - Ferreyra, Raúl Gustavo (2024)
Written version of the oral presentation given on August 30, 2024, during the awarding of the honorary doctorate from the University of Buenos Aires to Gilmar Ferreira Mendes. The ceremony took place in the Red Room of the Faculty of Law.